Vital Members in the More Dysbiotic Oropharyngeal Microbiotas in H7N9-Infected Patients - Zha, Hua; Lu, Haifeng; Wu, Jieyun; Chang, Kevin; Wang, Qiangqiang; Zhang, Hua; Li, Jinyou; Luo, Qixia; Lu, Yanmeng; Li, Lanjuan (Frontiers in Medicine, 2020)
The dysbiosis of oropharyngeal (OP) microbiota is associated with multiple diseases, including H7N9 infection. Different OP microbial colonization states may reflect different severities or stages of disease, and affect the effectiveness of the treatments. Current study aims to determine the vital bacteria that could possibly drive the OP microbiota in the H7N9 patients to more severe microbial dysbiosis state. The OP microbiotas of 42 H7N9 patients and 30 healthy subjects were analyzed by a series of bioinformatic and statistical analyses. Two clusters of OP microbiotas in H7N9 patients, i.e., Cluster_1_Diseased and Cluster_2_Diseased, were determined at two microbial colonization states by Partition Around Medoids (PAM) clustering analysis, each characterized by distinct operational taxonomic units (OTUs) and functional metabolites. Cluster_1_Diseased was determined at more severe dysbiosis status compared with Cluster_2_Diseased, while OTU143_Capnocytophaga and OTU269_Treponema acted as gatekeepers for both of the two clustered microbiotas. Nine OTUs assigned to seven taxa, i.e., Alloprevotella, Atopobium, Megasphaera, Oribacterium, Prevotella, Stomatobaculum and Veillonella, were associated with both H7N9 patients with and without secondary bacterial lung infection in Cluster_1. In addition, two groups of healthy cohorts may have potential different susceptibilities to H7N9 infection. These findings suggest that two OP microbial colonization states of H7N9 patients were at different dysbiosis states, which may help determine the health status of H7N9 patients, as well as the susceptibility of healthy subjects to H7N9 infection.